AKSES INFORMASI PEMBANGUNAN PERIKANAN PADA MASYARAKAT DI DESA MUARA PANTUAN KECAMATAN ANGGANA KABUPATEN KUTAI KARTANEGARA - Rahmad Fitri Yanto; Erwiantono; Qoriah Saleha (Jurnal Pembangunan Perikanan dan Agribisnis, 2020)
The purpose of this study was to determine the type of information needed by the fishing community in Muara Pantuan Village and determine the type of media used by the fishing community in Muara Pantuan Village. The entire study was carried out for 14 months. This research is a research that uses survey research methods (survey method). By taking 40 respondents using disproportional stratified random sampling in a community that is active, open and has been in contact with people or institutions outside their environment, the data analysis technique used is quantitative descriptive by describing the data state data of fishermen community objects in Muara Pantuan Village. The results showed that the type of information needed by the fishing community in Muara Pantuan Village was aquaculture technology and capture fisheries technology, while the type of media used by the fishing community in Muara Pantuan Village was interpersonal media and electronic media. Interpersonal media in the form of communication between fellow fishermen is the most commonly used media in the Muara Pantuan Village, while the electronic media most frequently used is a mobile telephone in the form of wireless communication that connects the community in Muara Pantuan Village with the community outside the Muara Pantuan Village. Keywords: Access, Information, Media, Estuary Pantuan.